Time-dependent occurrence of false-positive results of opiate test strips after CAFFETIN® use - Atanacković, Milica; Baralić, Katarina; Ćurčić, Marijana; Javorac, Dragana; Buha Djordjević, Aleksandra; Antonijević Miljaković, Evica; Antonijević, Biljana; Bulat, Zorica; Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
Opioids are a wide group of natural, semi-synthetic and synthetic substances, used in the pharmacotherapy of painful conditions. However, due to their psychoactive properties, they are often abused. Immunochromatographic test panels are used for substance abuse monitoring and are quick, simple and based on the principle of competitive binding. Main disadvantage of immunochromatographic analysis is cross-reactivity, because of sufficient specificity of test antibodies for the analyte of interest. This study aimed to examine the effect of codeine-based OTC preparation (Caffetin®) on false positive results of preliminary opiate urineanalysis, and determine the time period during which these results may occur. The study included two female healthy subjects, 23 and 24 years old. One of them administered double oral dose of Caffetin® (two tablets - total of 20 mg of codeine) and the other administred single oral dose of Caffetin® (one tablet - 10mg of codeine). Urine samples were collected for 48h. Analysis was performed by AmeritekOPI® monocomponent test strips and DOAMultiGnost 3 Test Panel® multicomponent test strips. The use of Caffetin® gave false positive results for opiates after 4,7h (Subject 1) and 3,3 h (Subject 2). The first negative result occurred after 39h (Subject 1) and 37,9h (Subject 2). After application of codeine-based OTC preparations, false positive results were obtained in less than 48h. Literature data indicate that positive results on opiates might occur 48h after consuming of codeine-based medication. Hence, it is necessary to carry out further research with aim to avoid doubts during interpretation of immunochromatographic test results.